Effects of liraglutide on metabolic syndrome in WBN/Kob diabetic fatty rats supplemented with a high‐fat diet. Issue 1 (16th March 2020) - Kaji, Noriyuki; Takagi, Yoshiichi; Matsuda, Satomi; Takahashi, Anna; Fujio, Sakurako; Asai, Fumitoshi
Abstract: Background: Liraglutide, a GLP‐1 receptor agonist, has recently been used to treat metabolic syndrome (MS) because of its anti‐diabetic and anti‐obesity effects. We have previously shown that Wistar Bonn Kobori diabetic and fatty (WBN/Kob‐Lepr fa, WBKDF) rats fed a high‐fat diet (HFD) developed MS including marked obesity, hyperglycemia, and dyslipidemia. To obtain further information on WBKDF‐HFD rats as a severe MS model, we performed a pharmacological investigation into the anti‐MS effects of liraglutide in this model. Methods: Seven‐week‐old male WBKDF‐HFD rats were allocated to three groups (N = 8 in each group): a vehicle group, a low‐dose liraglutide group, and a high‐dose liraglutide group. They received subcutaneous injections of either saline or liraglutide at doses of 75 or 300 μg/kg body weight once daily for 4 weeks. Results: Results showed that liraglutide treatment reduced body weight gain and food intake in a dose‐dependent manner. The marked hyperglycemia and the glucose tolerance were also significantly ameliorated in the liraglutide‐treated groups. Moreover, liraglutide also reduced the plasma triglyceride concentration and liver fat accumulation. Conclusions: The present study demonstrated that liraglutide could significantly alleviate MS in WBKDF‐HFD rats, and the reaction to liraglutide is similar to human patients with MS. WBKDF‐HFD rats are therefore considered to be a useful model for research on severe human MS.